MODEL PEMBELAJARAN SERTA MEDIA PEMBELAJARAN BAHASA INDONESIA DI JENJANG SD/MI - Dita Ayu Khoerunnisa; Alifh Alamsyah; Arif Sanjaya; Nurfitria (Bajang Institute, 2024)
The meaning of the learning model is a framework that provides a systematic description for carrying out learning activities, in order to help students achieve learning objectives in accordance with a predetermined curriculum. Where this makes the learning model different from the learning method that has implemented steps or learning approaches that are even broader in scope. The number of learning methods varies, so it takes special concentration for SD / MI teachers in choosing and determining which method is better. So that with the spirit of teacher creativity demanded by the times and technological developments. Indonesian language learning media in elementary schools (SD) basically teaches children to be able to communicate or use Indonesian well and correctly. Learning Indonesian in elementary schools is necessary to improve students' ability to communicate in Indonesian well and correctly, both orally and in writing. Elementary schools have the aim of creating or preparing students to have the ability to continue and increase their knowledge to a higher level of education. One of the efforts or efforts made to realize and achieve this goal is to improve and grow student learning achievement